The monetary model of the exchange rate: A structural interpretation - Mathias Moersch; Dieter Nautz (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1998)
We emphasize the importance of properly identifying the long-run relations underlying the monetary model of the exchange rate. The separate estimation of long-run money demands leads to a 'structural' error correction equation which allows an interpretation of the various channels affecting the exchange rate in the monetary model. We apply this approach to the analysis of the DM/Dollar exchange rate where the structural model yields better results than various alternative forecast strategies, among them a random walk.
urn:nbn:de:kobv:11-10056404
Keywords: 330